ПУТИ ОПТИМИЗАЦИИ ДИАГНОСТИКИ И ЛЕЧЕНИЯ ОСТРОГО ВАРИКОТРОМБОФЛЕБИТА - O. B. Nuzova; Yu. A. Sobolev; Yu. Yu. Solodov; A. A. Chegodaeva; Yu. S. Batalova (Acta Biomedica Scientifica)
The clinical studies involved. 27 operated patients with acute varicothrombophlebitis treated in the department of vascular surgery of Orenburg Municipal Clinical Hospital named after N.I. Pirogov in 2011-2012. We proved the necessity of control ultrasound examination of veins of lower extremities at the varicothrombophlebitis in 1 and 7 days after admission to the hospital to diagnose the thrombosis progress despite of clinical manifestations of the disease. This allows to carry out the sapheno-femoral crossectomy promptly and. to prevent the risk of development of pulmonary thromboembolism.